Triage test for all-oral drug-resistant tuberculosis (DR-TB) regimen: a phase IV study to assess effectiveness, feasibility, acceptability and cost-effectiveness of the Xpert MTB/XDR assay for rapid triage and treatment of DR-TB - Kogieleum Naidoo; Derek J Sloan; Wilber Sabiiti; Bariki Mtafya; Stephen H Gillespie; Aderonke Agbaje; Nyanda Elias Ntinginya; Morten Ruhwald; Agnes Gebhard; Anushka Naidoo; Rubeshan Perumal; Getachew Tollera; et al. (BMJ Open)
Introduction The TriAD study will assess the Xpert MTB/XDR (Xpert XDR; Cepheid) assay to detect tuberculosis (TB) drug resistance in sputum testing positive for TB to rapidly triage and treat patients with a short all-oral treatment regimen.Methods and analysis In this study, approximately 4800 Xpert MTB/RIF or Ultra MTB-positive patients (irrespective of rifampicin (RIF) resistance (RR) status) from several clinical sites across South Africa, Nigeria and Ethiopia will be enrolled over 18–24 months and followed-up for approximately 6 months post-TB treatment completion. Participants will be enrolled into one of two cohorts based on Xpert MTB/RIF and Xpert XDR results: Mycobacterium tuberculosis (M.tb) positive participants with RR in Cohort 1 (n=880) and M.tb positive RIF susceptible TB patients with isoniazid mono-resistance irrespective of presence of resistance to fluoroquinolones, second-line injectable drugs or ethionamide in Cohort 2 (n=400). Cohort 1 will be compared with historical cohorts from each implementing sites. The primary study outcomes include time to initiation of an appropriate treatment regimen by resistance profile and the proportion of patients with favourable treatment outcomes compared with historical cohorts from each of the implementing sites. Secondary outcomes include feasibility, acceptability and cost-effectiveness of this approach to inform policies and guidelines for programmatic implementation of this triage and treat model for drug-resistant tuberculosis management. Utility of the tuberculosis molecular bacterial load assay (TB-MBLA) for real-time treatment response assessment will also be evaluated.Ethics and dissemination The University of KwaZulu-Natal Biomedical Research Ethics Committee (BREC) and local research committees have provided ethical review and approval (BREC/00002654/2021, HREC 210805, NHREC/01/01/2007 and EPHI-IRB-459–2022). The South African Health Products Regulatory Authority (SAHPRA) have granted regulatory approval for the TRiAD Study (SAHPRA MD20211001). Trial results will be disseminated through conference presentations, peer-reviewed publications and the clinical trial registry.Trial registration number Clinicaltrials.gov; Trial registration number: NCT05175794; South African National Clinical Trials Register (SANCTR DOH-27-012022-4720)